Geosynthetics for sustainable cities: 3D models and mechanical damage - Lucas, Paiva (2022)
Geosynthetics have increasingly been used as a reinforcement material in a variety of geotechnical engineering applications (e.g., roadways, foundations, steep slopes). Reinforced soil relies on the transference of stresses from the soil to the reinforcement elements. Thus, it is key to understand how mechanical damage of the geosynthetics influences the stress-strain-time response of soil-geosynthetic interaction. This thesis includes collecting high-quality experimental data and performing laboratory tests on the deformation response of geosynthetics and soil-geosynthetic composite, before and after damage. Then, numerical tests, using the finite element method will be implemented with relevant constitutive equations. The tests will be validated using the experimental data collected. Parametric numerical tests will be performed. Finally, a general approach will be described to model common geosynthetic structures, for a more efficient use of both geosynthetics and natural resources.